Pedagogy of the protest: teaching social workers about collective action and the social policy context - Mariam Zaidi; HÃ¥vard Aaslund (Social Work and Society, 2022)
Social workers are frequent participants in social movements that affect social policy. However, social workers may be inadequately prepared for challenging aspects of social movements such as collective protest. This conceptual study critically examines the political dimension of social welfare through a comparative analysis of Norway and the United States. We discuss the dilemmas in political engagement that social workers encounter, followed by suggestions for social workers' response to collective action. Using the example of Black Lives Matter, we explore social work education and framing to prepare social workers for collective protests and offer a framework that provides direction for social work practice.